Cells of the Immune System 2020
DOI: 10.5772/intechopen.86598
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the T Lymphocyte Immune Response via Secretome Produced miRNA: From Tolerance Induction to the Enhancement of the Anticancer Response

Abstract: T cells are key mediators of graft tolerance/rejection, development of autoimmunity, and the anticancer response. Consequently, differentially modifying the T cell response is a major therapeutic target. Most immunomodulatory approaches have focused on cytotoxic agents, cytokine modulation, monoclonal antibodies, mitogen activation, adoptive cell therapies (including CART cells). However, these approaches do not persistently reorient the systemic immune response thus necessitating continual therapy. Previous m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
64
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(70 citation statements)
references
References 74 publications
(97 reference statements)
6
64
0
Order By: Relevance
“…The core component of the biomanufacturing system is, in essence, a twoway mixed lymphocyte reaction (MLR) in which MHC-disparate leukocyte populations (either human PBMC or murine splenocytes) are co-incubated. Previous work from our laboratory demonstrated that the covalent grafting (PEGylation) of methoxy(polyethylene glycol) [mPEG] to one leukocyte population resulted in abrogation of the MHC-mediated proliferation of Teff cells [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. Moreover, these studies demonstrated that, consequent to impaired cell:cell communication (Figure 4C), the weak allostimulation induced a tolerogenic/anergic state both in vitro and in vivo ( Figure 4A) [29][30][31][32][33][34]41].…”
Section: A New Approach To the Biomodulation Of The Treg:teff Ratiomentioning
confidence: 93%
See 4 more Smart Citations
“…The core component of the biomanufacturing system is, in essence, a twoway mixed lymphocyte reaction (MLR) in which MHC-disparate leukocyte populations (either human PBMC or murine splenocytes) are co-incubated. Previous work from our laboratory demonstrated that the covalent grafting (PEGylation) of methoxy(polyethylene glycol) [mPEG] to one leukocyte population resulted in abrogation of the MHC-mediated proliferation of Teff cells [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. Moreover, these studies demonstrated that, consequent to impaired cell:cell communication (Figure 4C), the weak allostimulation induced a tolerogenic/anergic state both in vitro and in vivo ( Figure 4A) [29][30][31][32][33][34]41].…”
Section: A New Approach To the Biomodulation Of The Treg:teff Ratiomentioning
confidence: 93%
“…As demonstrated in Figure 7A, the onset and incidence of diabetes was assessed and correlated with the Treg:Teff ratio of the mice [31][32][33][34][35]. As shown, 75% of the untreated NOD mice, but only 40% of the TA1 treated mice, developed T1D.…”
Section: Treatment Of Autoimmune Diseases Via Treg:teff Modulationmentioning
confidence: 95%
See 3 more Smart Citations